Conflict and Cooperation in the Global Commons : a Comprehensive Approach for International Security - Jasper, Scott (Georgetown University Press, 2012)
More than ever, international security and economic prosperity depend upon safe access to the shared domains that make up the global commons: maritime, air, space, and cyberspace. Together these domains serve as essential conduits through which international commerce, communication, and governance prosper. However, the global commons are congested, contested, and competitive. In the January 2012 defense strategic guidance, the United States confirmed its commitment "to continue to lead global efforts with capable allies and partners to assure access to and use of the global commons, both by strengthening international norms of responsible behavior and by maintaining relevant and interoperable military capabilities." In the face of persistent threats, some hybrid in nature, and their consequences, Conflict and Cooperation in the Global Commons provides a forum where contributors identify ways to strengthen and maintain responsible use of the global commons. The result is a comprehensive approach that will enhance, align, and unify commercial industry, civil agency, and military perspectives and actions.